Usefulness of Discarded Vitreous Samples from Routine Vitrectomy - Natàlia Vilà; Pablo Zoroquiain; Vasco Bravo-Filho; Emilia Antecka; Helena Dietrich; John C. Chen; I. John Galic; Michael A. Kapusta; Miguel N. Burnier (Journal of Ophthalmology)
Purpose. To describe the histopathological features of vitreous samples obtained after vitrectomy surgery from diabetic and nondiabetic patients. Methods. Vitreous specimens from 137 patients who underwent vitrectomy for different clinical conditions were analysed. All samples were centrifuged and each resulting pellet was fixed and processed as part of routine paraffin section histopathology. The histopathological features were categorized in a semiquantitative fashion. The samples from diabetic and nondiabetic patients were compared. Results. The 125 included patients (58 diabetic, 60% males) were aged 64.2±13.9 years. The presence of hemorrhage, inflammatory cells, and histiocytes was significantly higher in the diabetic group (P<0.001, P=0.028, and P=0.016, resp.), showing more vessels (P<0.001) and ghost vessels (P=0.049). The presence of inflammatory cells was the feature with the highest sensitivity for detecting diabetes mellitus (98%) and also the highest negative predictive value (89%). In the multivariate analysis, three variables emerged as independent significant predictors of diabetes in vitrectomy samples: hemorrhage, endothelial-lined vessels, and age (P<0.001, P<0.001, and P=0.019, resp.). Conclusions. Different histopathological features can be found in vitreous samples from diabetic patients. Analysis of vitrectomy samples may serve as a tool for diabetes management.